Jr Thermal Comfort Analysis of Design Element in El’s Coffee Roastery Building Bandar Lampung: A Case Study of the Use of Glass Facades in a Tropical Climate : A Case Study of the Use of Glass Facades in a Tropical Climate - A. F. abdullah; D. Lisa (Journal of Engineering and Scientific Research, 2026)
Indonesia's tropical climate, characterized by high humidity, hot temperatures, and intense solar radiation year-round, demands a more adaptive and thoughtful architectural design approach. In this context, building designers need to consider the balance between aesthetics and thermal comfort for space users. The use of glass, for example, can provide abundant natural lighting and enhance a building's visual character, but it can also increase the heat load of interior spaces if not equipped with appropriate mitigation strategies. Therefore, implementing effective air circulation, such as air conditioning devices, shading devices, and reflective protective coatings, is crucial to reducing excess heat. Facade design that is responsive to tropical climates is key to achieving optimal building performance. This study examines the thermal comfort analysis and application of architectural design elements to the El's Coffee Roastery building in Bandar Lampung, with a particular focus on the function and quality of the glass facade as a key element influencing the building's appearance and performance in a tropical climate.